2022
DOI: 10.3390/nu14235119
|View full text |Cite
|
Sign up to set email alerts
|

Beetroot Juice Produces Changes in Heart Rate Variability and Reduces Internal Load during Resistance Training in Men: A Randomized Double-Blind Crossover

Abstract: Beetroot juice (BJ) has been used as a sport supplement, improving performance in resistance training (RT). However, its effect on the modulation of the autonomic nervous system has not yet been widely studied. Therefore, the objective of this randomized double-blind crossover study was to assess the effect of acute BJ supplementation compared to placebo in blood pressure (BP), heart rate (HR), heart rate variability (HRV) and internal load during RT measure as Root Mean Square of the Successive Differences be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 96 publications
0
2
0
Order By: Relevance
“…Interventional studies have shown that the consumption of vegetables rich in nitrates such as lettuce, rocket, chard, spinach, cabbage, radish or beetroot may alleviate symptoms of acute vascular dysfunction, as well as reduce periodontal inflammation [10,[19][20][21]. Nitrates taken up with the diet are accumulated by the salivary glands, resulting in salivary concentrations 10-20 times higher than plasma levels [22,23].…”
Section: Impact Of Dietary Nitrate On the Recovery Of Therapy-related...mentioning
confidence: 99%
“…Interventional studies have shown that the consumption of vegetables rich in nitrates such as lettuce, rocket, chard, spinach, cabbage, radish or beetroot may alleviate symptoms of acute vascular dysfunction, as well as reduce periodontal inflammation [10,[19][20][21]. Nitrates taken up with the diet are accumulated by the salivary glands, resulting in salivary concentrations 10-20 times higher than plasma levels [22,23].…”
Section: Impact Of Dietary Nitrate On the Recovery Of Therapy-related...mentioning
confidence: 99%
“…In type 2 diabetes, beetroot juice not only controls glucose, but also lowers lipid metabolism and lowers blood pressure [16][17].…”
Section: Connection Of the Publication With Planned Research Workmentioning
confidence: 99%